Predicting Financial Distress In Companies Listed On The Indonesia Sharia Stock Index (ISSI): An Examination Of The Zmejewski, Springate, And Altman Models - Achmad, Achmad; hayet, hayet (ITB AAS INDONESIA Surakarta, 2024)
Financial distress is a state that indicates the downward trend in an enterprise’s cash flow that occurs to bankruptcies. The purpose of this study is to compare the predictive model Altman, Zmijewski, and Springate in order to determine the parameters of corporate financial traouble. 24 manufacturing firms included in the Indonesia Islamic Stoc Index made up the sample. The study’s finding demonstrated that the prediction model was successful in identifying the financial difficulties of the business. Among the models, the Zmijewski model has the highest accuracy and thus the best model performance.